Barriers that prevent the practice of physical activity in older adults: systematic review (Revista Chilena de Rehabilitación y Actividad Física, 2023)
To systematically review the literature of qualitative studies, focusing on the identification of barriers that older adults perceive to engage in physical activity. The review covered databases such as Redalyc, PubMed, Science Direct, EBSCO, Dialnet and the journal Human Kinetics. Those articles who had adults older than 60 years were considered. Fifteen articles were analyzed, finding a total of 20 barriers divided into three domains: a) intrapersonal; b) interpersonal and c) community domain. It was found that in the intrapersonal domain the two main barriers were lack of time and fear; in the interpersonal, the most outstanding were, without physical activity partners and lack of social support, finally, the domain of the community, a bad climate and the cost of participating stood out among the most important barriers to the practice of physical activity.
Keywords: Interpersonal Relations; Aging; Leisure Time Activities; Health Policy